A visibly transparent radiative cooling film with self-cleaning function produced by solution processing. (10th November 2021) - Chen, Guoliang; Wang, Yaming; Qiu, Jun; Cao, Jianyun; Zou, Yongchun; Wang, Shuqi; Ouyang, Jiahu; Jia, Dechang; Zhou, Yu
Highlights: A multifunctional film with visibly transparent radiative cooling and self-cleaning was designed. The film was fabricated by a low-cost and scalable solution processing method. The films can spontaneously cool and clean the daylighting structures. Abstract: Daylighting structures, including solar cells and building windows, utilize sunlight whilst suffering from undesired solar heat and outdoor dust contamination. A radiative cooling system that is transparent to sunlight and has a superhydrophobic surface would cool and clean the daylighting structures in a sustainable manner. However, the majority of the current daytime radiative cooling systems were designed to fully reflect the incident sunlight to maximize the cooling power. In this work, we optimized both the sunlight transmission and infrared thermal irradiation by modeling the size-dependent scattering and absorption of light by SiO2 spheres embedded in a polymer matrix, we found that the use of nanospheres (20 nm) enabled both high sunlight transmittance (> 90%) and infrared emissivity (~0.85). This theoretical prediction was confirmed by experimental measurements of a solution-processed nanocomposite film. When coated on a solar cell, the as-prepared film not only preserved the power conversion efficiency of the cell (14.71%, uncoated cell has an efficiency of 14.79%) but also radiatively cooled the cell by up to 5 °C under direct sunlight. This reduction of the operating temperature of the solar cell further enhanced its electrical power output, evidenced by an increase in the equilibrium temperature of the LED load by about 14 °C. The nanoscale textured surface formed by the nanospheres further led to superhydrophobicity and thus excellent self-cleaning performance (efficient removal of dust by wind and/or water droplets).